Turbulent heat transfer to separation nanofluid flow in annular concentric pipe - Togun, Hussein; Kazi, Salim Newaz; Badarudin, Ahmad (Elsevier, 2017)
Turbulent heat transfer to separation nanofluid flow in annular concentric pipe were studied numerically and experimentally. In the numerical study, finite volume method with standard k-ε turbulence model in three dimensional domains was selected. Three different types of water based (Al2O3, CuO, TiO2) nanofluids were employed in this simulation. The adopted boundary conditions were, expansion ratio (ER = 1.25, 1.67, and 2), Reynolds number ranging from 20, 000 to 50, 000, water based nanofluids used Al2O3, CuO, TiO2with volume fractions varied between 0 and 2% at different heat fluxes, varied from 4000 W/m2to 16, 000 W/m2. For experimental study, Al2O3water based nanofluid was used to validate the numerical results. The results show that the volume fraction of nanofluid and Reynolds number significantly affect the surface heat transfer coefficient; an increase in surface heat transfer coefficient was noted when both volume fraction of nanofluids and Reynolds number were increased for all the cases. The improvement of heat transfer was about 36.6% for pure water at the expansion ratio of 2 compared to heat transfer obtained in a straight pipe. Augmentation of heat transfer could be achieved by using nanofluid at expansion ratio 2 where the total improvements were about 45.2% (TiO2), 47.3%(CuO), and 49%(Al2O3). Also the increment in the pressure drop was about 42% for pure water at expansion ratio 2 compared with straight pipe whereas by using nanofluid they were 62.6% (TiO2), 65.4% (CuO) and 57.6% (Al2O3). Good agreements were observed between numerical and experimental results all the way.